Energy consumption and intestinal microbiome disorders of yellow catfish (Pelteobagrus fulvidraco) under cold stress - Hu, Junru; Zhao, Hongxia; Wang, Guoxia; Sun, Yuping; Wang, Lei (Frontiers in Physiology, 2022)
Cold stress is an environmental factor that negatively impacts warm-water fish. One such economically-relevant freshwater fish that is found in China, i.e., the yellow catfish (Pelteobagrus fulvidraco), cannot tolerate cold stress. Understanding the physiological and biochemical mechanisms under cold stress may provide insights for improving yellow catfish management in the cold. Therefore, we investigated the metabolic and gut microbiota changes in cold stress in response to induced cold stress. We found that cold stress in yellow catfish leads to a significant increase in the consumption of glucose and triglycerides, as well as increased use of cholesterol as an alternate energy source. Moreover, cold stress also upregulated several significant biological processes in the fish such as thermogenesis, oxidative phosphorylation, the spliceosome machinery, RNA transport, protein processing that occurs in the ER, and purine and pyrimidine metabolism pathways involved in energy production. On the other hand, many other mechanisms like insulin resistance, starch and sucrose metabolism, and the glyoxylate and dicarboxylate metabolic pathways that also served as energy production pathways were significantly downregulated. Furthermore, organic acids and their derivatives as well as the lipids and lipid-like molecules were mainly altered in cold stress; Prenol lipids, steroids, and their derivatives were significantly upregulated, while fatty acyls and glycerophospholipids were significantly down-regulated. Integrated analysis of transcriptomic and metabolomic data revealed that carbohydrate metabolism, lipid metabolism, amino acid metabolism, and nucleotide metabolism were involved in cold stress resistance. In addition, the intestinal microbiota composition was also altered, suggesting that cold stress also impaired intestinal health. This research study could offer insights into winter management or the development of feed to promote cold resistance in yellow catfish.